2020
DOI: 10.1002/biof.1613
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Alkannin represses growth of pancreatic cancer cells based on the down regulation of miR‐199a

Abstract: Alkannin displays tumor suppressive activity by initiating apoptosis. Here, we corroborated its role in pancreatic carcinoma (PANC-1) cells and addressed the molecular mechanism in which microRNA-199a (miR-199a) and Klotho might be implicated. PANC-1 and MIN6 cells were treated by alkannin and its role was evaluated in cellular viability. Next we assessed the ability of PANC-1 cells to proliferate, migrate, and invade as well as apoptosis process. Besides, proliferating cell nuclear antigen (PCNA), CyclinD1, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Our study found that alkannin inhibited the activation of AKT signaling by upregulating PTEN. Regarding how alkannin regulates PTEN, previous reports suggested that alkannin reduces the expression levels of some microRNAs, including miR‐4461, miR‐199a, and miR‐9, that have been reported to target PTEN 7,8,23,31–33 . Hence, we speculated that alkannin might regulate PTEN expression through multiple pathways, such as the miRNA–mRNA axis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our study found that alkannin inhibited the activation of AKT signaling by upregulating PTEN. Regarding how alkannin regulates PTEN, previous reports suggested that alkannin reduces the expression levels of some microRNAs, including miR‐4461, miR‐199a, and miR‐9, that have been reported to target PTEN 7,8,23,31–33 . Hence, we speculated that alkannin might regulate PTEN expression through multiple pathways, such as the miRNA–mRNA axis.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding how alkannin regulates PTEN, previous reports suggested that alkannin reduces the expression levels of some microRNAs, including miR-4461, miR-199a, and miR-9, that have been reported to target PTEN. 7,8,23,[31][32][33] Hence, we speculated that alkannin might regulate PTEN expression through multiple pathways, such as the miRNA-mRNA axis. The detailed mechanism of alkannin in CSCC needs to be clarified by performing more in-depth experiments in the future.…”
Section: Alkannin Promoted Pten Expression In Cscc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin inhibited prostate cancer progression by regulating the miR-30a-5p/PCLAF axis [ 15 ]. In addition, alkannin has been found to inhibit the growth of pancreatic cancer cells by downregulating miR-199a [ 16 ]. Here, the interaction between alkannin and miR-4461 was investigated in OC.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds show a wide range of significant pharmacological activities, such as antibacterial, 2 anti-inflammatory, 3 antifungal, 4 and antitumor. [5][6][7][8] Many methodologies on their total synthesis have been described. [9][10][11][12] Nicolaou 13 reported a concise and efficient total synthesis of alkannin and shikonin, in which a novel protecting system for the masking of 5,8-dihydroxy-1,4-naphthoquinones was used and 4-methyl-1-(naphtho[1,8-de:4,5-d'e'] bis( [1,3]dioxine)-4-yl)pent-3-en-1-one (5) (Scheme 1) served as a key intermediate.…”
Section: Introductionmentioning
confidence: 99%